A WWW-based learning environment to complement a university course on neural networks - Martins, L. (2013)
Web Based Learning is increasingly attracting the interest of several teaching Institutions. It provides mechanisms for improving the conventional learning process, and also allows the opportunity for reaching new students, throughout the world, by just using an Internet connection. This paper describes a tool that is being built in the University of Algarve, to complement an optional course on Neural Networks. This tool incorporates multimedia material to explain visually important concepts, integrates Matlab, and will allow self-assessment and automatic student marking.